Informed health choices intervention to teach primary school children in low-income countries to assess claims about treatment effects: process evaluation. Issue 9 (11th September 2019) - Nsangi, Allen; Semakula, Daniel; Glenton, Claire; Lewin, Simon; Oxman, Andrew D; Oxman, Matt; Rosenbaum, Sarah; Dahlgren, Astrid; Nyirazinyoye, Laetitia; Kaseje, Margaret; Rose, Christopher James; Fretheim, Atle; et al.
Abstract : Background: We developed the informed health choices (IHC) primary school resources to teach children how to assess the trustworthiness of claims about the effects of treatments. We evaluated these resources in a randomised trial in Uganda. This paper describes the process evaluation that we conducted alongside this trial. Objectives: To identify factors affecting the implementation, impact and scaling up of the intervention; and potential adverse and beneficial effects of the intervention. Methods: All 85 teachers in the 60 schools in the intervention arm of the trial completed a questionnaire after each lesson and at the end of the term. We conducted structured classroom observations at all 60 schools. For interviews and focus groups, we purposively selected six schools. We interviewed district education officers, teachers, head teachers, children and their parents. We used a framework analysis approach to analyse the data. Results: Most of the participants liked the IHC resources and felt that the content was important. This motivated the teachers and contributed to positive attitudes. Although some teachers started out lacking confidence, many found that the children's enthusiasm for the lessons made them more confident. Nearly everyone interviewed thought that the children learnt something important and many thought that it improved their decision-making. The main barrier to scaling up use of the IHC resources that participants identified was the need to incorporate the lessons into the national curriculum. Conclusion: The mostly positive findings reflect the trial results, which showed large effects on the children's and the teachers' critical appraisal skills. The main limitations of this evaluation are that the investigators were responsible for both developing and evaluating the intervention.